Wds-Mediated H3K4me3 Modification Regulates Lipid Synthesis and Transport in Drosophila. - Zhao, T.; Wang, M.; Li, Z.; Li, H.; Yuan, D.; Zhang, X.; Guo, M.; Qian, W.; Cheng, D. (International journal of molecular sciences, 2023)
Lipid homeostasis is essential for insect growth and development. The complex of proteins associated with Set 1 (COMPASS)-catalyzed Histone 3 lysine 4 trimethylation (H3K4me3) epigenetically activates gene transcription and is involved in various biological processes, but the role and molecular mechanism of H3K4me3 modification in lipid homeostasis remains largely unknown. In the present study, we showed in Drosophila that fat body-specific knockdown of will die slowly (Wds) as one of the COMPASS complex components caused a decrease in lipid droplet (LD) size and triglyceride (TG) levels. Mechanistically, Wds-mediated H3K4me3 modification in the fat body targeted several lipogenic genes involved in lipid synthesis and the Lpp gene associated with lipid transport to promote their expressions; the transcription factor heat shock factor (Hsf) could interact with Wds to modulate H3K4me3 modification within the promoters of these targets; and fat body-specific knockdown of Hsf phenocopied the effects of Wds knockdown on lipid homeostasis in the fat body. Moreover, fat body-specific knockdown of Wds or Hsf reduced high-fat diet (HFD)-induced oversized LDs and high TG levels. Altogether, our study reveals that Wds-mediated H3K4me3 modification is required for lipid homeostasis during Drosophila development and provides novel insights into the epigenetic regulation of insect lipid metabolism.